GLOBALIZATION and Marketing of innovative culture - I. Alyoshina (Вестник университета)
In the situation of globally slowing economic growth and of the necessity for overcoming Russian economy’s system crisis the importance of Russian Federation’s cultural innovativeness is declared. The importance of socio-cultural environment development for creation and using competitive technologies is augmented. Interconnected levels of culture - national, organizational, individual, - are described as being increasingly influenced by internationalization and globalization. For innovative dimension enforcement the necessity of education, as of a social institute’s modernization is shown. The recommendations on education’s innovativeness as of a sphere of country’s environment for cultural matrix formation for the future of RF are presented in part of deformalization and internationalization.